Effect of Combined Spiritual Tapping and Music Therapy (Spirtus) on Depressive Symptoms among Elderlies at Banteran Village - Rohmani, Lisa Qoriana; Kusumawardani, Lita Heni; Rahayu, Eva (Journal of Bionursing, 2024)
Background: Elderly is someone who has reached the age of 60 years and over and is an age group that is vulnerable to experiencing health problems such as depression. One non-pharmacological treatment that can be used to treat this problem is a combination of spiritual tapping therapy and music therapy. This study aimed to determine the effect of a combination of spiritual tapping therapy and music therapy (SPIRTUS) on symptoms of depression in the elderly in Banteran Village. Objective: Knowing the effect of the combination of Spiritual Tapping therapy and Music therapy (SPIRTUS) on symptoms of depression in the elderly in Banteran Village. Method: This research was a case study with a quantitative approach, pretest-posttest without a control group. Respondents were 3 elderly people with severe depression in Banteran Village. The intervention was given for a duration of ±30 minutes per day for 7 days. Data analysis used the Wilcoxon test. Results: In this study, giving SPIRTUS therapy was proven to be able to reduce the GDS score in the elderly from severe depression (score 9-11) to moderate depression (score 5-8). The results of the analysis using the Wilcoxon test showed a sig. (2-tailed) value of 0.109 (p > 0.05), which means there was no significant difference between the pre and post results of administering SPIRTUS therapy to elderly people who experienced depression. Conclusion: The combination of Spiritual Tapping and Music Therapy (SPIRTUS) can be applied to elderly clients and proven to be able to reduce symptoms of depression in the elderly by paying attention to the 5 keys to therapeutic success.